Extracts of Caesalpinia ferrea and Trichoderma sp. on the control of Colletotrichum sp. transmission in Sideroxylon obtusifolium seeds - P.A.F.R. MELO; E.U. ALVES; C.C. MARTINS; A.P. ANJOS NETO; K.M.S. PINTO; L.R. ARAÚJO; C.P. VIEIRA; L.C. NASCIMENTO
ABSTRACT Recent research reports the importance of preserving plants in Brazilian semiarid regions, in this context, the scientific literature has reported different pharmacological studies from plant extracts with an antifungal potential, coming from forest species that can contribute as a control and management strategy in the transmission of phytopathogens. This study aimed to evaluate the effect of biotech treatments in controlling the transmission of Colletotrichum sp. in seeds of S. obtusifolium. In this study, 100 seeds were subjected to the following preventive treatments: fungicide Captan®, extract of Caesalpinia ferrea Mart. Ex. Tul., and biological control with Trichoderma spp. The biological control with Trichoderma spp. and the alternative control using C. ferrea extract provided a greater protection to seeds and seedlings of S. obtusifolium facing the transmissibility of Colletotrichum sp.The treatment based on plant extract is more efficient for this purpose only in large seeds and does not interfere on the germination percentage and speed. Therefore it is necessary to perform other studies with Trichoderma spp. and C. ferrea extract to test different doses of these products.